The entrepreneur's choice: Venture capital debt financing with adverse selection - G. Geoffrey Booth; Orkunt Dalgic; Allan Young (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
This paper studies the consequences of using a debt contract to raise venture capital for an entrepreneurial project in an adverse selection setting with different quality venture capitalists. The paper considers not only the likelihood of success of a one-time project being dependent on the quality of the venture capitalist, but also the problem of a reduced ownership value of future rents from the venture if the venture capitalist takes it over as the result of default of the entrepreneur. Expressions for the face value of debt required for pooling and separating equilibria are also derived. The existence of a separating equilibrium with bad quality venture capitalists is used to show how less reputable venture capitalists can survive in the marketplace. Finally, the paper uses a numerical example to demonstrate why the entrepreneurs of more profitable entrepreneurial firms may prefer to do business with bad quality venture capitalists.
Keywords: 650